Landform analysis of the Pueyrredón Lake area in northwestern Santa Cruz, Argentina - Horta, Luis Rubén (2013)
The aim of this research was to analyze the landforms around Pueyrredón Lake (NW Santa Cruz in Argentina) to contribute to the understanding of the paleoenvironmental evolution of Patagonia during the Late Pleistocene–Early Holocene. The Pueyrredón Lake area belongs to the Patagonian shield, northwest of the Santa Cruz Province (47°22′28″ S–71°55′34″ W). Characteristic landforms were identified through satellite images (Landsat 7 ETM) and field work. These landforms include glacial troughs, glacier striations and groove casts, three fan deltas on the south margin of Pueyrredón Lake, lacustrine and glacio-lacustrine sediment, and till deposits. In addition, short detailed stratigraphic logs were measured for paleoenvironmental analysis, and several sedimentary deposits were sampled to characterize grain size variations. All of the information is displayed on a geomorphological map. The modern and ancient landforms were also analyzed based on their topographic characteristics, which were determined by a digital elevation model (DEM). Geomorphological conditions of the erosional and depositional processes in the paleoglacial environment were analyzed using longitudinal- and cross-sections. The results shed light on the climatic variability during the most recent geological period. Major changes in the landscape morphology were associated with glacier evolution and the development and division of the great lakes in the eastern Andes, in Central Patagonia.